Efficiency of Farm Management in Potato Crop Production Farms in the South and East of Tripoli - Waseem Mohamed Albhilil , Ragib Mansour Elwerfeli , Souad Khalil Elbandagou (Journal of Pure & Applied Sciences, 2018)
This study aimed to analyze the efficiency of farm management in the farms of the eastern and southern regions of Tripoli, and this can be achieved through a set of the following objectives : (1) Identification of the levels of production and economic efficiency of potato crop in the study area. (2) Estimation of the possible increase in the value of the potato crop production in the study area. (3) Reaching a set of recommendations stemming from the obtained results which can be useful in the development of agricultural policy and the preparation of agricultural economic programs in this field. To reach their objectives the study adopted the analysis of production efficiency using the income and cost criteria for potato crop, and the method of non-parametric analysis using DEA (Data Envelopment Analysis) method, according to the concept of CRS (Constant Returns to Scale)  and VRS (Variance Returns to Scale), SE (Scale Efficiency) for Potato Crop.The results of the study indicated that: The relative profitability in the sample of East Tripoli and the sample of the south of Tripoli was about 26.67 and 15.06 respectively, while the ratio of revenues to costs was about 1.24 and 1.14 respectively. As for the criterion of return on the invested dinar, it was about 0.24, 0.14 respectively. It was appear that the average technical productivity efficiency of the potato crop production in the sample of the study according to the Constant Returns to Scale, Variance Returns to Scale and Scale Efficiency  reached about 0.954, 0.905, 0.865 in eastern of Tripoli, Tripoli whereas it is reached about 0.907, 0.937, 0.968 in southern of Tripoli.